Determinants of Consumption Expenditure Levels among Migrant Students: The Role of Frugal Living, Allowance, and Purchasing Power - llstianah, Esa; Bakhri , Syaeful; Busthomi, Achmad Otong (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2026)
Purpose – This study aims to analyze the influence of frugal living, allowance, and purchasing power on migrant students' expenditure levels, with consumption patterns as a mediating variable. The study is motivated by the financial constraints commonly experienced by migrant students in managing limited resources to meet daily needs. Methodology – A quantitative research design was employed. The population consisted of migrant students in Cirebon City, with 100 respondents selected using purposive sampling. Data were collected through structured questionnaires. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Findings – The results indicate that frugal living, allowance, and purchasing power significantly affect expenditure levels, both directly and indirectly through consumption patterns (p < 0.05). Consumption patterns have a significant impact on expenditure and act as a mediating variable, strengthening the relationship between frugal living, allowance, purchasing power, and expenditure. These findings suggest that expenditure behavior among migrant students is influenced not only by financial capacity but also by frugal attitudes and priority-based consumption. Novelty – This study offers originality by incorporating frugal living and consumption patterns as key variables in explaining student expenditure, extending previous research that primarily focused on income-related factors. Significance – The findings provide practical insights for migrant students in managing personal finances and serve as a reference for educational institutions and policymakers in designing effective financial literacy and student welfare programs.